An Episode in Allyship Responding to the Uprising (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
In the midst of dual pandemics, the racial justice uprising and the Coronavirus pandemic, I, a black associate professor of education, took on the challenge of having my white colleague as an apprentice for racial justice work. While co-teaching a critical diversity course, I decided to strategically engage our College of Education in a robust conversation on racial equity and reconciliation. An unanticipated event in that process was that my apprentice would become an effective ally and co-conspirator. I share this insight of our process in hopes that aspiring allies might improve their effort.